2022
DOI: 10.3390/cells11162588
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of Cellular Senescence Induced by Temozolomide in Glioblastoma Cells: Search for Senolytics

Abstract: A first-line therapeutic for high-grade glioma, notably glioblastoma (GBM), is the DNA methylating drug temozolomide (TMZ). Previously, we showed that TMZ induces not only apoptosis and autophagy, but also cellular senescence (CSEN). We presented the hypothesis that GBM cells may escape from CSEN, giving rise to recurrent tumors. Furthermore, the inflammatory phenotype associated with CSEN may attenuate chemotherapy and drive tumor progression. Therefore, treatments that specifically target senescent cells, i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 72 publications
3
11
0
Order By: Relevance
“…Since TIS involves the increased expression of BCL-2, targeting BCL-2 may exert anticancer effects. BCL2-targeting drugs, including ABT-737 and ABT-263 (navitoclax), natural substances, such as artesunate, fisetin, and curcumin, showed senolytic effects in glioblastoma cells and non-transformed cells [ 83 , 167 ]. ABT-263 eliminated senescent cells and enhanced the efficacy of olaparib, a PARP inhibitor, in both breast and ovarian cancer cell lines [ 168 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since TIS involves the increased expression of BCL-2, targeting BCL-2 may exert anticancer effects. BCL2-targeting drugs, including ABT-737 and ABT-263 (navitoclax), natural substances, such as artesunate, fisetin, and curcumin, showed senolytic effects in glioblastoma cells and non-transformed cells [ 83 , 167 ]. ABT-263 eliminated senescent cells and enhanced the efficacy of olaparib, a PARP inhibitor, in both breast and ovarian cancer cell lines [ 168 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility for PCa patients with ATM mutations is the therapeutic application of ATM inhibitors, such as AZD1390, AZD0156, M4076, Ku 60019 or XRD-0394, but these inhibitors are still in clinical phase I studies. However, the combination of the DNA-methylating drug, temozolomide, with the ATM inhibitor, KU60019, has been shown to result in an increased induction of apoptosis in glioblastoma cells in vitro [ 52 ]. Furthermore, Fischer et al showed that PTEN mutant non-small-cell lung cancer requires ATM to suppress proapoptotic signaling and evade radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…297 Other well-demonstrated senolytics being tested for cancer treatment are inhibitors of BCL-2 family members. For example, ABT-737 and ABT-263 were shown to selectively kill senescent cells and blunt the recurrent growth and aggressiveness of cancer cells via interference with BCL-2, BCL-XL, and BCL-W. 291,298,299 Other BCL-XL inhibitors, such as A-1331852 and A-1155463, have also exhibited senolytic activity, 300,301 even though their efficacy in tumor therapy has not been confirmed. Using single-cell RNA sequencing, Martina Troiani and her colleagues identified novel senolytic targets that were essential for the survival of senescent tumor cells.…”
Section: Senolyticsmentioning
confidence: 99%
“…ABT‐737, navitoclax, chloroquine, ATMi, ATRi, BV‐6, PX‐866 and the natural compounds fisetin and artesunate exhibit senolytic activity, inducing death in senescent cells more efficiently than in proliferating cells. 299 …”
Section: Exploiting Senescence For Cancer Therapymentioning
confidence: 99%